Answer:
Option A is correct (17,11).
Step-by-step explanation:
6x - 9y = 3
3x - 4y =7
it can be represented in matrix form as![\left[\begin{array}{cc}6&-9\\3&4\end{array}\right] \left[\begin{array}{c}x\\y\end{array}\right] = \left[\begin{array}{c}3\\7\end{array}\right]](https://tex.z-dn.net/?f=%5Cleft%5B%5Cbegin%7Barray%7D%7Bcc%7D6%26-9%5C%5C3%264%5Cend%7Barray%7D%5Cright%5D%20%5Cleft%5B%5Cbegin%7Barray%7D%7Bc%7Dx%5C%5Cy%5Cend%7Barray%7D%5Cright%5D%20%3D%20%5Cleft%5B%5Cbegin%7Barray%7D%7Bc%7D3%5C%5C7%5Cend%7Barray%7D%5Cright%5D)
A=
X= ![\left[\begin{array}{c}x\\y\end{array}\right]](https://tex.z-dn.net/?f=%5Cleft%5B%5Cbegin%7Barray%7D%7Bc%7Dx%5C%5Cy%5Cend%7Barray%7D%5Cright%5D)
B= ![\left[\begin{array}{c}3\\7\end{array}\right]](https://tex.z-dn.net/?f=%20%5Cleft%5B%5Cbegin%7Barray%7D%7Bc%7D3%5C%5C7%5Cend%7Barray%7D%5Cright%5D)
i.e, AX=B
or X= A⁻¹ B
A⁻¹ = 1/|A| * Adj A
determinant of A = |A|= (6*-4) - (-9*3)
= (-24)-(-27)
= (-24) + 27 = 3
so, |A| = 3
Adj A=
A⁻¹ =
/3
A⁻¹ = ![\left[\begin{array}{cc}-4/3&3\\-1&2\end{array}\right]](https://tex.z-dn.net/?f=%5Cleft%5B%5Cbegin%7Barray%7D%7Bcc%7D-4%2F3%263%5C%5C-1%262%5Cend%7Barray%7D%5Cright%5D%20)
X= A⁻¹ B
X= ![\left[\begin{array}{cc}-4/3&3\\-1&2\end{array}\right] *\left[\begin{array}{c}3\\7\end{array}\right]](https://tex.z-dn.net/?f=%5Cleft%5B%5Cbegin%7Barray%7D%7Bcc%7D-4%2F3%263%5C%5C-1%262%5Cend%7Barray%7D%5Cright%5D%20%2A%5Cleft%5B%5Cbegin%7Barray%7D%7Bc%7D3%5C%5C7%5Cend%7Barray%7D%5Cright%5D)
X= ![\left[\begin{array}{c}(-4/3*3) + (3*7)\\(-1*3) + (2*7)\end{array}\right]](https://tex.z-dn.net/?f=%5Cleft%5B%5Cbegin%7Barray%7D%7Bc%7D%28-4%2F3%2A3%29%20%2B%20%283%2A7%29%5C%5C%28-1%2A3%29%20%2B%20%282%2A7%29%5Cend%7Barray%7D%5Cright%5D)
X= ![\left[\begin{array}{c}-4+21\\-3+14\end{array}\right]](https://tex.z-dn.net/?f=%5Cleft%5B%5Cbegin%7Barray%7D%7Bc%7D-4%2B21%5C%5C-3%2B14%5Cend%7Barray%7D%5Cright%5D)
X= ![\left[\begin{array}{c}17\\11\end{array}\right]](https://tex.z-dn.net/?f=%5Cleft%5B%5Cbegin%7Barray%7D%7Bc%7D17%5C%5C11%5Cend%7Barray%7D%5Cright%5D)
x= 17, y= 11
solution set= (17,11).
Answer:
Step-by-step explanation:
Answer:
1/2
Step-by-step explanation:
Given:
(2 cubed) (2 superscript negative 4)
= (2³)(2^-4)
= (2³) (1 / 2⁴)
= (2³ * 1) / 2⁴
= 2³ / 2⁴
Both numerator and denominator has the same base. Thus, pick one of the bases
Also, in indices, division sign can be translated to subtraction
Therefore,
2³ / 2⁴
= 2^3-4
= 2^-1
= 1/2¹
= 1/2
(2³)(2^-4) = 1/2
$771
The answer is below in the picture as well
Did you just say that you are a beautiful boy and that we should send you a message? WHAT?!!!!??